Scenario Economic Impact Analysis of Offshore Fishing Tournaments in Ocean City - Chi, Yeong Nain (International Journal of Business, Economics and Management, 2018)
This study used scenario analysis to estimate the economic impact of the expenditures of anglers who participated in offshore fishing tournaments in Ocean City, Maryland. The primary purposes of this study were to evaluate impacts on the adjacent areas, to identify potential uses for economic impact information, and to provide justification for investment and support of programs related to the needs of coastal communities and issues related to marine recreational fisheries management. To accomplish this study, the IMPLAN modeling system was employed to calculate the economic impact of offshore fishing tournaments on local and regional economies. Preliminary results using scenario analysis suggested the total economic impact of offshore fishing tournaments in Ocean City could be nearly 2.2 million for Wicomico and Worchester counties. To get this estimate, three different scenarios were considered based on potential expenditure estimate of what each tournament party would spend on lodging, fuel, food, fishing and miscellaneous costs. Using IMPLAN, impact metric categories could be generated including general labor income, job opportunities - employment, and value added. This paper provides the extent to which fishery managers, municipalities, business and private sector stakeholders could benefit from local marine recreational fishing tournaments, and potentially justify investment in infrastructure which supports marine recreational fishing.